Coupling Device and Distal Femoral Replacement for Periprosthetic Supracondylar Femur Fractures with an Ipsilateral Total Knee and Hip Replacement. Issue 1 (February 2014) - Grosso, Matthew J.; Lipman, Joseph; Bostrom, Mathias P.
Background: Periprosthetic supracondylar fractures in the setting of an ipsilateral total knee and hip replacement are a rare but serious orthopedic challenge. Description of Technique: In this unique situation, we consider insertion of a custom coupling device with a distal femoral replacement as an appropriate surgical solution that allows for stability and preserves hip and knee functionality, while not relying on the poor healing potential of the remaining intercalary femoral bone. Patients and Methods: We report the outcomes of two patients who underwent this custom coupling procedure. Results: These custom devices resulted in successful outcomes with restoration of ambulatory function and range of motion at greater than 14 months follow-up. Conclusions: We found that this technique provides sufficient stability and preserves functionality in a difficult-to-treat patient population. The results indicate that this technique may be considered as an alternative to more invasive procedures including total femoral replacement and complete femoral allograft constructs.